2016
DOI: 10.1002/2015ja021971
|View full text |Cite
|
Sign up to set email alerts
|

On the utility of the ionosonde Doppler‐derived EXB drift during the daytime

Abstract: Vertical EXB drift measured using the ionosonde Doppler sounding during the daytime suffers from an underestimation of the actual EXB drift because the reflection height of the ionosonde signals is also affected by the photochemistry of the ionosphere. Systematic investigations have indicated a fair/good correlation to exist between the C/NOFS and ionosonde Doppler‐measured vertical EXB drift during the daytime over magnetic equator. A detailed analysis, however, indicated that the linear relation between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…So our motive in this paper is not to discuss about daytime vertical drifts. While we present here daytime vertical drifts as well for brevity, however, a detailed study on daytime vertical drifts and their possible corrections are investigated in a separate paper by Joshi and Sripathi []. We present here drifts during evening hours when photoionization is minimum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…So our motive in this paper is not to discuss about daytime vertical drifts. While we present here daytime vertical drifts as well for brevity, however, a detailed study on daytime vertical drifts and their possible corrections are investigated in a separate paper by Joshi and Sripathi []. We present here drifts during evening hours when photoionization is minimum.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that their PRE drift variations are in good agreement with solar flux variations. More recently Joshi and Sripathi [] have studied the daytime vertical drifts by using ionosonde, and a correction factor is being identified and is applied based on neural network technique. These drifts were also compared with C/NOFS ion drifts and EEJ strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the IED varying with time passing by is partly ascribed to the solar orbit changes. Solar azimuth (AZI) and elevation (ELE) are calculated according to the observer local time and position (Wang et al 2013;Joshi and Sripathi 2016), and as the input parameters, they are expressed similarly as the UT variable:…”
Section: Input Parametersmentioning
confidence: 99%